2013
DOI: 10.1016/j.jped.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a protocol proposed by the Brazilian National Health Surveillance Agency for antibiotic use in very low birth weight infants

Abstract: The implementation of the protocol allowed improvement of sepsis diagnosis by reducing the diagnosis of probable early-onset sepsis, thus promoting efficient antimicrobial use in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…This management by risk assessment is unusual in Brazil, notably for VLBW infant sepsis evaluation, 9 , 10 and the authors hypothesize that this evaluation tends to have a significant impact on reducing the use of antibiotics in very low birth weight infants. Thus, this study aimed to evaluate the rates of culture-confirmed sepsis (CCS) and presumed EONS, as well as rates of ruled out neonatal sepsis (ROS) cases and rate of newborns not exposed to antibiotics in the first 48 h of life (NEATB), in the period from 2006 to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…This management by risk assessment is unusual in Brazil, notably for VLBW infant sepsis evaluation, 9 , 10 and the authors hypothesize that this evaluation tends to have a significant impact on reducing the use of antibiotics in very low birth weight infants. Thus, this study aimed to evaluate the rates of culture-confirmed sepsis (CCS) and presumed EONS, as well as rates of ruled out neonatal sepsis (ROS) cases and rate of newborns not exposed to antibiotics in the first 48 h of life (NEATB), in the period from 2006 to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty studies were identified that described aspects of guideline implementation or health systems strengthening to improve outcomes of preterm babies in LMICs [ 59 , 63 , 104 , 128 , 130 , 135 , 142 , 144 , 145 , 157 , 177 , 178 , 180 , 181 , 188 , 191 , 197 - 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a particular indicator is analyzed, the reasons for the poor performance are identified which may include any number of health system bottlenecks. QI intervention studies found that simple interventions such as creation of a stepdown unit, involving mothers in infant care, and new antibiotic protocol reduced mortality in NICU [ 36 , 37 ]. Based on SQCI scores, in our intervention, similar actions were introduced in SNCU having low birth weight survival.…”
Section: Discussionmentioning
confidence: 99%